-2x-7(c+3)=-93

Simple and best practice solution for -2x-7(c+3)=-93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-7(c+3)=-93 equation:


Simplifying
-2x + -7(c + 3) = -93

Reorder the terms:
-2x + -7(3 + c) = -93
-2x + (3 * -7 + c * -7) = -93
-2x + (-21 + -7c) = -93

Reorder the terms:
-21 + -7c + -2x = -93

Solving
-21 + -7c + -2x = -93

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + -7c + 21 + -2x = -93 + 21

Reorder the terms:
-21 + 21 + -7c + -2x = -93 + 21

Combine like terms: -21 + 21 = 0
0 + -7c + -2x = -93 + 21
-7c + -2x = -93 + 21

Combine like terms: -93 + 21 = -72
-7c + -2x = -72

Add '2x' to each side of the equation.
-7c + -2x + 2x = -72 + 2x

Combine like terms: -2x + 2x = 0
-7c + 0 = -72 + 2x
-7c = -72 + 2x

Divide each side by '-7'.
c = 10.28571429 + -0.2857142857x

Simplifying
c = 10.28571429 + -0.2857142857x

See similar equations:

| 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x | | 4(2x-7)+4=8 | | 3x+4y-z=4 | | 4x+9=10x+3 | | -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 | | 3(y-6)=8y+22 | | P-3=11 |

Equations solver categories